Changing income inequality and structural transformation: The case of Botswana 1921 - 2010 - Ellen Hillbom; Jutta Bolt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
In Sub-Saharan Africa we find some of the highest levels of income inequality in the world. Nevertheless, we generally know very little about the historical development of inequality. In this paper we look at how inequality developed in colonial and post-colonial Botswana. We show that income inequality started rising in the 1940s and peaked in the mid-1970s about the time that the economy switched from cattle to diamonds. Since the 1990s, it has then declined somewhat. Following the tradition of Kuznets we discuss how this rise and decline could be related to a potential structural transformation of the economy.
Keywords: N00; D63; O14; 330; Africa; income inequality; structural transformation